2008
DOI: 10.1097/prs.0b013e3181706f87
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of the Three-Dimensional Structure of the Nasal Septum in Patients with Alveolar Clefts and Alveolar-Palatal Clefts

Abstract: The nasal septa present different three-dimensional morphologic patterns between the patients with alveolar clefts only and those with alveolopalatal clefts. This difference should be considered when performing surgical treatments for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…Examinations with computer tomography (CT) have also revealed reduced nasal airway size in CLP patients [4]. An association between the severity of the cleft and the degree of the nasal septum deviation has been found in patients with UCLP examined by CT [5]. However, Reiser et al [6] found no correlation between initial cleft size and nasal airway size and airflow in patients treated for UCLP.…”
Section: Introductionmentioning
confidence: 99%
“…Examinations with computer tomography (CT) have also revealed reduced nasal airway size in CLP patients [4]. An association between the severity of the cleft and the degree of the nasal septum deviation has been found in patients with UCLP examined by CT [5]. However, Reiser et al [6] found no correlation between initial cleft size and nasal airway size and airflow in patients treated for UCLP.…”
Section: Introductionmentioning
confidence: 99%
“…CT and CBCT are mainly used for planning orthognathic surgery before and after treatment and for assessing anatomical differences in the nose [47], [56], [79], [81], [85]. These techniques are also used for treatment planning and measuring the results of bone grafting [30], [33][35], [46], [64], [73], [75], [77], [78], [89].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its clinical importance, a wide range of studies concerning its treatment [1][2][3][4][5], morphological analysis [6], diagnosis [7], and aetiology [8], has been reported. Despite extensive research, few studies exist about the risk of facial fracture in patients with unilateral complete cleft palate.…”
Section: Introductionmentioning
confidence: 99%